Heat and Moisture Anomalies During Crop Failure Events in the Southeastern Australian Wheat Belt - Hao Li; Jessica Keune; Qiqi Gou; Chiara M. Holgate; Diego Miralles (Earth's Future, 2024)
Abstract Prolonged droughts and heatwaves are common causes of agricultural failure in Australia, yet the origins of these climate anomalies remain understudied. Here, we use a Lagrangian trajectory model driven by atmospheric reanalysis and constrained by satellite data to unravel the sources of precipitation and heat over the Southeastern Australia wheat belt. Furthermore, we assess the impact of local and upwind drought conditions on the moisture and heat imports to the region. Results indicate that the most extreme crop failure events over the wheat belt (i.e., 1994, 2002, and 2006) were associated with persistent high‐pressure systems. The ocean provided on average 72% of the moisture for precipitation and 39% of the heat arriving over the wheat belt, with the moisture sources substantially decreasing during crop failure events. Upwind drought further intensified rainfall deficits and heat stress during these events due to lower moisture and higher heat imports to the region. This was particularly clear during the initial phase of the Millennium Drought in 2002. Then, yield deficits exceeded 50%, and ∼4% of the precipitation originated from drought‐affected regions upwind, compared to the 9% that was expected climatologically from those regions. Simultaneously, the heat import from these regions upwind increased by ∼10 W m−2, from the climatological 23%–25%, during this event. While these results indicate a limited potential for upwind land management to mitigate downwind agricultural loss in the Southeastern Australia wheat belt, other agricultural regions with a higher climatic dependency on remote land may benefit from such strategies.